A survey of the understanding on root canal disinfection among dental students in Kulliyyah of Dentistry, IIUM. - Nik Muhammad Nasir, Nik Norfathiah; Mohamad Yusoff, Siti Nurbatrisya; Ahmad, Norfaezah; Mustaffa, Musliana (Malaysian Endodontic Society, 2019)
Introduction: Insufficient evidence in root canal disinfection contributes to differences in clinical practice. Previous surveys have been conducted on general dental practitioners and endodontists but on the undergraduate dental students are not present. This study aimed to assess the understanding on root canal disinfection among IIUM dental students and to come out with a guideline for root canal disinfection procedure in students’ clinics.